Spanish double passives and related structures - Bosque, Ignacio; Gallego, Ángel J. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
This paper studies the properties of a previously unnoticed passive construction found in some varieties of present day Spanish. Such construction, which we refer to as double passive (following NGRALE 2009), contains two adjacent passive complexes (Ese producto fue empezado a ser usado como conservante, Eng. That product was started to being used as a preservative), but only one of them is interpretable as a bona fide passive. We discuss the properties of this structure, suggesting that the passive (i.e., participial) morphology of the aspectual predicate (i.e., fue empezado) is uninterpretable, and obtained through a mechanism of agreement at a distance (Chomsky’s 2000, 2001 Agree).